CUSTOMER RELATIONSHIP MANAGEMENT INFORMATION SYSTEM ST BORROMEUS HOSPITAL - Bunardi, Jimmy; Angreani, Linda Salma (Department of Informatics Engineering, 2012)
Customer Relationship Management Information System St.Borromeus Hospitalis anapplication to process data related to the promotion, marketing and cooperation between the St.Borromeus Hospita lwith the Contractor. Data processing is not optimum cooperation with the contractorat the Marketing division of Borromeus Hospital,cause search of information about the contractor, take a bit longer so that hamper the process of promotion and marketing. Therefore it need an application that can support and solve the problem.Based on these problems the author intends arrange final by taking the title of